Pengaruh Olahraga Terhadap Kesehatan Mahasiswa Fakultas Pendidikan Olahraga Dan Kesehatan Universitas Pendidikan Indonesia - Teuku Rama Alfarisal; Muhamad Husen; Sinatria Putra Pamungkas; Ahmad Fua’din (JIPOR: Jurnal IPTEK Olahraga dan Rekreasi, 2023)
Humans live with hundreds of complex immune systems with hundreds of components that support and work together to protect each other's members and body functions. To maintain health, humans need to increase self-awareness in carrying out physical activities. Physical fitness is a person's main point in achieving optimal health, when health and exercise are balanced, their involvement will be mutually beneficial, the results of persistent exercise can increase a number of positive things in the body, for example, when humans are experiencing a lot of stress, psychological health can reduce brain function, however exercise will improve the performance of brain function and the body's immune system, of course it will eliminate stress, not only that, exercise can reduce cholesterol levels in the body, exercise is not about lifting heavy equipment and physical activities that are full of stress, but exercise can be simplified by brisk walking, exercise, running and cycling. The results of a person's physical training will definitely experience significant differences, depending on the time and habits of the individual in training their physical body. Because the more frequently and regularly you exercise, the higher your individual productivity and fitness will be. So the aim of this research is to find out how important the influence of sport is on the health of students at the Faculty of Sports and Arts Education.